MANAGING THE SUPPLY CHAIN WITH LEAN AND THEORY OF CONSTRAINTS IN CONTINUOUS PROCESS INDUSTRY: CASE SSAB EUROPE - Uotila, Eero (My University, 2016)
Lean and Theory of Constrains (TOC) are probably the two best known management paradigms, managerial philosophies and production approaches in the modern manufacturing context. The goal is to find the similarities and differences between two approaches and compare the performance of the production approaches in an experimental simulation study. This constitutes the first research question. The objective of the research is to give the case company a comprehensive picture of the current research-based knowledge regarding Lean and TOC and it will also examine Lean and TOC’s theoretical applicability for Manufacturing-To-Order continuous process industry such as steel production. The client of this thesis is a steel production group SSAB’s division called SSAB Europe. The previous constructs the second research question. Third and fourth research questions consider the experimental simulation study related matters such as a shift system change and increase in the Train’s (Raahe-Hämeenlinna) coil transferring capacity. Empirical part of the thesis was influenced by both quantitative and qualitative research approaches and the empirical part of the thesis was implemented as an experimental simulation case study. More specifically, the empirical part was conducted with the help of discrete simulation software called ProcessModel. The experimental arrangement could be described as a structured experimental arrangement, where all the experimental results were saved. From the simulations, three metrics were gathered: throughput, Work-In-Process and Utilization. The results analysis indicated that there could be detected both similarities and differences between Lean and TOC production approaches. Secondly the literature review as well as the simulations indicated that Lean may not be applicable to the Manufacturing-To-Order steel production environment. The simulations proved that in terms of the total supply chain performance, the shift system changes and the increase in Train’s transfer capacity had positive impact on the performance of the supply chain.
Keywords: Supply chain; Inventory; Control; Bottleneck; Throughput; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|